2018
DOI: 10.14669/am.vol82.art1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fuel on the energy consumption and production of greenhouse gases in transport

Abstract: Nowadays, the environmental aspects of transport are very actual issues, mainly the energy consumption and GHG production. The priority of EU transport strategy is to decrease the negative environmental impacts of all transport modes. The article discusses the calculation of the energy consumption and production of greenhouse gases in transport from both the primary and secondary points of view. This means, that it reflects the implications on the environment not only while operating the vehicle, but also duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They are quiet, accelerate dynamically [49] and do not emit any pollutants into the atmosphere where they are used [5]. An increasing number of customers are buying electric vehicles because of their ecology [6,10]. The origin of electricity intended for charging electric cars is very important.…”
Section: Introductionmentioning
confidence: 99%
“…They are quiet, accelerate dynamically [49] and do not emit any pollutants into the atmosphere where they are used [5]. An increasing number of customers are buying electric vehicles because of their ecology [6,10]. The origin of electricity intended for charging electric cars is very important.…”
Section: Introductionmentioning
confidence: 99%
“…This means that these items may directly or indirectly collect, process and/or exchange data via a computer network and the Internet. Concurrently, other growing trends on a global scale are the advances in electromobility [2][3][4][5][6][7][8][9], obtaining energy from renewable sources and alternative fuels [10][11][12][13][14][15][16] and reducing exhaust emissions from means of transport [17][18][19][20][21][22][23][24]. The analysis of the literature and the state of knowledge confirmed that there are many technologies on the market for obtaining data from photovoltaic systems, electric car chargers and electricity meters taken from the power grid [2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen can also be produced using RES [27]. This approach contributes to the reduction of greenhouse gas emissions by means of transport [4,5]. Environmental awareness encourages both individual customers and vehicle fleet owners [7,16] to purchase low-emission or zero-emission vehicles.…”
Section: Introductionmentioning
confidence: 99%